METODE JOURNALING UNTUK MENGATASI WRITER’S BLOCK PENULIS PEMULA DI PROGRAM STUDI PENERBITAN - Refi Yuliana; Suratni; Prily Fitria Aziz (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
This research aims to provide alternative solutions to the writer’s block problem commonly faced by novice writers. Writer’s block is a condition where a writer experiences a dead end in completing a work in the middle of the writing process. This is a psychological problem faced by most writers. This research describes steps that can be taken if beginner writing experiences stagnation, namely through journaling techniques. This method is expected to be able to provide solutions to novice writers in the Publishing Study Program who are compiling their Final Assignment work in the form of a Fiction book or Novel. The results of this research found that the journaling method was carried out in 3 main stages. The first is the initial writing development stage which applies a 3-act structure, the second is the journalling stage which is carried out on plot chapters that experience obstacles, and the third stage, where the writer continues writing the main manuscript. The conclusion of this research is that the need for relaxation in writing for novice writers can be done through the journaling method